Disruption of running activity rhythm following restricted feeding in female mice: Preventive effects of antidepressants - Kazumi Miyawaki; Hiroaki Araki; Hiroyuki Yoshimura (Elsevier, 2015)
Biological rhythms are critical in the etiology of mood disorders; therefore, effective mood disorder treatments should address rhythm disturbances. Among the variables synchronized with the light-dark cycle, spontaneous activity in rodents is useful for investigating circadian rhythms. However, previous studies have focused only on the increase of wheel-running activity under restricted feeding conditions, while little information is available on circadian rhythm of running activity. In this study, chronometrical analysis was used to assess whether circadian rhythms during wheel-running are altered by restricted feeding and affected by antidepressant drugs. Wheel revolutions were automatically recorded and analyzed using cosinor-rhythmometry in 8-week old ICR albino mice. When feeding was restricted to 1 h per day (21:00-22:00), wheel-running rhythms were reliably disrupted. Female mice exhibited marked alterations in the pattern and extent of wheel-running beginning on day 1. Subchronic treatment with imipramine or paroxetine, as well as tandospirone and (−)-DOI, prevented wheel-running rhythm disruption. Thus, altering the circadian activity rhythms of female mice on a 1-h feeding schedule may be useful for investigating disturbances in biological rhythms.